Protocol for a qualitative study on the online connections of people with ME/CFS and the relationship between these online connections and offline lives - Qulsom Fazil; Anna Lavis; Diane Louise Shortland (BMJ Open)
Introduction Myalgic encephalomyelitis (ME), also known as chronic fatigue syndrome (CFS), is a debilitating chronic illness that affects the central nervous and immune systems, causing core symptoms of extreme fatigue, post-exertional malaise, cognitive issues and sleep disturbance. With reported higher online use than in other chronic illnesses, people with ME/CFS are often housebound and isolated and may struggle to maintain social relationships. Due to a lack of biomarkers, the illness is often contested, causing invalidation and stigma for those affected. This study aims to broaden the knowledge on how people with ME/CFS gain online connections and whether and how these connections integrate into and impact their everyday life.Methods and analysis Qualitative interviews will be conducted with adults aged over 18 years with a diagnosis or self-diagnosis of ME or CFS (n=20–25). A semi-structured topic guide will be used to interview participants and explore online connections and relationships between these and everyday life with ME/CFS. Interviews will be recorded and transcribed verbatim. Data will be thematically analysed to gain in-depth insight into this largely unexplored topic.Ethics and dissemination The study has ethical approval from the University of Birmingham (reference: RN_1722-Jun2024), and informed written consent will be provided by all participants. Findings will be published in peer-reviewed journals and disseminated to advocacy organisations and health professionals seeking to offer remote support for people with ME/CFS and their families. This study will provide crucial insight into online use and how it can guide the formulation of management plans for people who may currently receive no support from health professionals at all.